1996
DOI: 10.1017/s1355617700001673
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of neuropsychological functioning in Alzheimer's disease and frontotemporal dementia

Abstract: Neuropsychological changes distinguishing mild Alzheimer's disease (AD) from frontotemporal dementia (FTD) have been described, but empirical verification of differential cognitive characteristics is lacking. Archival neuropsychological data on 15 FTD patients, 16 AD patients, and 16 controls were compared. Controls outperformed both patient groups on measures of verbal and nonverbal memory, executive ability, and constructional skill, with AD patients showing more widespread memory decline. No differences wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
0
2

Year Published

1999
1999
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(105 citation statements)
references
References 18 publications
6
97
0
2
Order By: Relevance
“…The profiles of cognitive deficits exhibited by FTD and AD patients on the MDRS parallel those seen with more extensive testing. Several studies have shown greater memory impairment in AD than in FTD for both verbal (Elfgren et al, 1994;Kramer et al, 2003;Lindau et al, 1998;Perry & Hodges, 2000;Rosen et al, 2004;Thomas-Anterion et al, 2000) and visual (Frisoni et al, 1995;Kertesz et al, 2003a;Kramer et al, 2003;Pachana et al, 1996;Perry & Hodges, 2000) materials, a finding that has been attributed to greater medial temporolimbic pathology in AD (Braak & Braak, 1991) than in FTD (Frisoni et al, 1996;Lavenu et al, 1998). Similarly, a larger deficit in conceptual abilities in FTD than in AD has been shown on tests of conceptual processing and verbal abstraction (Kertesz et al, 2003a;Slachevsky et al, 2004).…”
Section: Cognitive Dysfunction In Ftdmentioning
confidence: 99%
See 2 more Smart Citations
“…The profiles of cognitive deficits exhibited by FTD and AD patients on the MDRS parallel those seen with more extensive testing. Several studies have shown greater memory impairment in AD than in FTD for both verbal (Elfgren et al, 1994;Kramer et al, 2003;Lindau et al, 1998;Perry & Hodges, 2000;Rosen et al, 2004;Thomas-Anterion et al, 2000) and visual (Frisoni et al, 1995;Kertesz et al, 2003a;Kramer et al, 2003;Pachana et al, 1996;Perry & Hodges, 2000) materials, a finding that has been attributed to greater medial temporolimbic pathology in AD (Braak & Braak, 1991) than in FTD (Frisoni et al, 1996;Lavenu et al, 1998). Similarly, a larger deficit in conceptual abilities in FTD than in AD has been shown on tests of conceptual processing and verbal abstraction (Kertesz et al, 2003a;Slachevsky et al, 2004).…”
Section: Cognitive Dysfunction In Ftdmentioning
confidence: 99%
“…It should be noted that studies of visuospatial and constructional abilities that have not shown a difference between FTD and AD often involve drawing the Rey-Osterrieth Complex Figure (Diehl et al, 2005;Frisoni et al, 1995;Kertesz et al, 2003a;Kramer et al, 2003;Pachana et al, 1996;Rosen et al, 2004), a task known to be influenced by attentional and strategicorganizational requirements dependent upon the frontal lobes (Varma et al, 1999). A second major finding from the present study is that FTD patients exhibit a faster rate of cognitive decline than those with AD when cognition is measured by the MDRS.…”
Section: Cognitive Dysfunction In Ftd 379mentioning
confidence: 99%
See 1 more Smart Citation
“…Pachana et al (1996), for example, noted that FTD patients were relatively more impaired on executive tasks and relatively less impaired in memory that AD patients, and Kramer et al (2003) reported that the relative patterns of impairment on executive, language, and memory measures were more discriminating than any individual test.…”
Section: Neurocognitive Features Of Ftdmentioning
confidence: 99%
“…2,5,6,11,[14][15][16] Patients with Alzheimer's disease and frontotemporal dementia do not have significant problems with constructional skill because their parietal regions remain intact. 3,4,8) However, few reports have investigated the effect of NPH on constructional skill, although the parietal regions are also affected.…”
Section: Discussionmentioning
confidence: 99%